Ta’ṡir Taṭbîq Waṣîlah al-Ta’lîm al-Lughah al-Arabiyyah “Factile” li Tarqiyyah Mahârah al-Istimâ’ - Zulfa Amalia; Junaedi Junaedi; Saefullah Azhari (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2022)
Purpose-The purpose of the researchers is to discuss the title "The Influence of the Application of Language Learning Media through Factile Games to Improve Listening Skills in Grade 8 Students at SMP Nurul Huda Surabaya". Design/Methodology/Approach- In order to be able to solve the problems found in grade 8 students at SMP Nurul Huda Surabaya, researchers used a quantitative approach with the percentage formula and T-test.  For data collection using methods: 1) observation, 2) interviews, 3) tests, and 4) documentation.  The sample technique used was purposive sampling technique, and the research subjects were class 8A with a total of 32 students Findings- The results of this study, there is an effect of applying language learning media through Factile games to improve listening skills in grade 8 students, this can be seen from the results of the "t" test, namely to (9.16) and tt(1.309 and 1.695) so Ha accepted and Ho rejected. Research Limitation/Implications- It is clear that this research has an effect on the application of language learning media through Factile games to improve listening skills in grade 8 students at SMP Nurul Huda Surabaya